2021
DOI: 10.1038/s41467-021-22491-8
|View full text |Cite|
|
Sign up to set email alerts
|

Common variants in Alzheimer’s disease and risk stratification by polygenic risk scores

Abstract: Genetic discoveries of Alzheimer’s disease are the drivers of our understanding, and together with polygenetic risk stratification can contribute towards planning of feasible and efficient preventive and curative clinical trials. We first perform a large genetic association study by merging all available case-control datasets and by-proxy study results (discovery n = 409,435 and validation size n = 58,190). Here, we add six variants associated with Alzheimer’s disease risk (near APP, CHRNE, PRKD3/NDUFAF7, PLCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 202 publications
(177 citation statements)
references
References 42 publications
7
153
1
Order By: Relevance
“…Even though the current AD application is based on a smaller sample size compared to recent AD GWAS, 15 , 23 , 24 , 34 , 35 , 36 it demonstrates the ability of the proposed Knockoffscreen-AL method to handle large biobank-scale data. Compared to the analysis of the UK Biobank data in Jansen et al., 15 the data version we used (March 2021 update of the UK Biobank resource) contains more reported AD-affected individuals (ICD10 code) and more reported parental AD (due to 2 nd visits for some participants), so our single-variant/window analysis is better powered.…”
Section: Discussionmentioning
confidence: 92%
“…Even though the current AD application is based on a smaller sample size compared to recent AD GWAS, 15 , 23 , 24 , 34 , 35 , 36 it demonstrates the ability of the proposed Knockoffscreen-AL method to handle large biobank-scale data. Compared to the analysis of the UK Biobank data in Jansen et al., 15 the data version we used (March 2021 update of the UK Biobank resource) contains more reported AD-affected individuals (ICD10 code) and more reported parental AD (due to 2 nd visits for some participants), so our single-variant/window analysis is better powered.…”
Section: Discussionmentioning
confidence: 92%
“…No nominally significant associations were found between the four COL4A1 variants and AD in a large meta‐GWAS study in the European population ( p > 0.05). 32 …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the suggestive common variants between AD and controls were also searched in a recent large meta‐genome‐wide association study (GWAS) in the European population. 32 …”
Section: Methodsmentioning
confidence: 99%
“…In particular, it has been reported that GPC2 levels in CSF resemble the status of adult hippocampal neurogenesis, decreasing over time according to preliminary studies [ 32 ]. Furthermore, a recent meta-analysis has shown a genome-wide significant statistical association with AD of the rs12705073 polymorphism, located in the first intron of the GPC2 gene [ 33 , 34 ]. The GPC2 homologue GPC5 has been shown to be downregulated in both CSF and plasma of Aβ negative MCI subjects when compared to control subjects in the Biofinder study [ 35 ]; HSPGs are present in amyloid lessons, promoting Aβ peptide and tau fibrillization and providing resistance against proteolytic breakdown [ 36 ].…”
Section: Discussionmentioning
confidence: 99%